Sistem Informasi Terpusat Berbasis Client Server Pada Yamaha Asli Motor VIII Tanjungpinang - Jajang Nurjaman; Slamet Santoso; Suhartono (Jurnal Bangkit Indonesia, 2019)
The sales, purchase and payroll processes at Yamaha Asli Motor VIII Tanjungpinang are currently processing data on incoming and outgoing goods as well as managing incoming and outgoing finances using manual methods. In order for the data processing process to run effectively and efficiently, it should be necessary to use information system applications to cope with and handle existing data processing processes. With the formation of a system with a computerized process, it is hoped that it can overcome the problems that have occurred. In conducting this research, the software development method used is the waterfall method which consists of systems engineering, analysis, design, implementation, testing and maintenance. This application is based on a client server and is built using the Java Netbeans programming language and the PhpMyAdmin database. The result of this research is a software system for data processing at Yamaha Asli Motor VIII Tanjungpinang. With this application, it is hoped that it will make it easier for Yamaha Asli Motor VIII Tanjungpinang in the data collection process.